Influence of Distal Reference Point of the Tibial Mechanical Axis on the Ankle and Hindlimb Alignment Change after Total Knee Arthroplasty - Kikuchi, Kenichi; Nakano, Naoki; Ishida, Kazunari; Kuroda, Yuichi; Hayashi, Shinya; Tsubosaka, Masanori; Kamenaga, Tomoyuki; Matsushita, Takehiko; Kuroda, Ryosuke; Matsumoto, Tomoyuki (The Journal of Knee Surgery, 2023)
The alignment philosophy in total knee arthroplasty (TKA) has tended to shift from the gold standard of mechanically aligned technique to personalized alignment, such as the kinematically aligned (KA) technique. However, the influences of different surgical techniques on lower limb alignment relative to the ground are not fully investigated. This study investigated the influence of the ankle and hindlimb alignment change after mechanically aligned TKA and KA-TKA. The varus osteoarthritic patients who underwent TKAs were divided into a mechanically aligned TKA group (group M, n = 50) and a KA-TKA group (group K, n = 50). Radiographic parameters (hip–knee–calcaneus [HKC] angle, hip–knee–ankle [HKA] angle, talar tilt angle [TTA], and tibiocalcaneal angle [TCA]) were investigated using full-length standing radiographs. The deviation angle (ΔTA; angle between the tibial mechanical axis [TMA] and the ground tibial mechanical axis [gTMA]) and the change of ΔTA (cΔTA) were also assessed. These parameters were compared between the two groups, along with the correlation between the preoperative HKA angle and other parameters. ΔTA, TTA, and TCA showed no differences between the groups pre- and postoperatively, and no significant changes were observed postoperatively. The preoperative HKA angle showed a significant negative correlation with cΔTA in both groups (group M: r = –0.33, p = 0.02; group K: r = –0.29, p = 0.04) although no correlation was observed the with preoperative TTA and TCA. Despite no change in ΔTA after surgery, the preoperative varus deformity was associated with a change in the deviation between gTMA and TMA after surgery. A severely varus knee may be inappropriate for ground KA-TKA.
Keywords: total knee arthroplasty; kinematic alignment; mechanical alignment; calcaneus; ground mechanical axis; ankle